EFFECTIVENESS STORYTELLING TECHNIQUE GROUP GUIDANCE SERVICES TO IMPROVE SPEAKING ETHICS IN CLASS VII STUDENTS OF STATE JUNIOR HIGH SCHOOLS 38 SAMARINDA ACADEMIC YEAR 2023/2024 - Handayani, Fitri; Hidayanto , Dwi Nugroho; Sari Pratiwi, Yasintha (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research is based on the results of a preliminary study at state junior high school 38 Samarinda showing a lack of speaking etiquette, with indicators that students often speak dishonestly, use inappropriate language, speak harshly, speak in a rude tone, and give nicknames to friends. This research aims to determine the effectiveness of storytelling technique group guidance services to improve speaking ethics. The type of research used is quantitative experiment. The experimental design used in this research was one group pretest - posttest. The population of all classes VII state junior high school 38 Samarinda with a total of 134 students and a sample of 7 students were identified as having low speaking ethics. The sampling technique used is Non-Probability Sampling with Purposive Sampling technique. The research results showed that before being given treatment the average score was 54%, after being given treatment the average score was 91% and the average score increased by 59.46%. Based on the T-test results, it is known that Sig. (2-tailed) has a value of 0.000 < 0.05, so it can be concluded that Ha is accepted, which means that there is an increase in speaking ethics in class VII students after receiving treatment in the form of storytelling technique group guidance services. So it can be concluded that storytelling technique group guidance services can be used to improve speaking ethics in class VII students at state junior high school 38 Samarinda for the 2023/2024 academic year.